Russian and Ukraine conflict effect the crude oil market and financial markets are examined from the perspectives of the countries that import and export crude oil. - Dr.George- Beaman; Dr. Federic-Kunt (Al-Qanṭara, 2023)
This essay examines how the conflict between Russia and Ukraine has affected the price of crude oil and the stock markets of both importing and exporting nations. We use a multi-fractal detrended fluctuation analysis (MF-DFA) to look at how well the crude oil market performed both before and after the conflict started. Additionally, using the technique of multi-fractal detrended cross-correlation analysis, we evaluate the cross correlations between the crude oil market and stock markets in the exporting and importing nations before and after the conflict (MF-DCCA). We conclude that the efficiency of the crude oil market has been lower after the Russia-Ukraine conflict than previously by measuring the generalized Hurst exponents, mass exponents, and multi-fractal spectrums. Keyword- Oil price, war conflict, financial market and countries economic growth.